Separators for electrochemical devices

JP7641732B2Active Publication Date: 2025-03-07JAPAN VILENE CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020203379
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-08
Publication Date
2025-03-07
Estimated Expiration
2040-12-08

AI Technical Summary

Benefits of technology

【0009】 本願出願人が検討した結果、「繊維構造体と無機粒子、ならびに、前記繊維構造体における一方の主面に前記無機粒子を担持しているバインダ成分とを備える、電気化学素子用セパレータであって、前記繊維構造体における前記一方の主面の比表面積は、前記繊維構造体におけるもう一方の主面の比表面積よりも小さい」電気化学素子用セパレータにおいて、本発明の構成を満足することによって、上述の問題を解決できることを見出した。この理由として、以下の効果が発揮されているためだと考えられる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641732000001
    Figure 0007641732000001
  • Figure 0007641732000002
    Figure 0007641732000002
  • Figure 0007641732000003
    Figure 0007641732000003
Patent Text Reader

Abstract

To provide an electrochemical element separator that can realize an electrochemical element with better electrical output characteristics.SOLUTION: In a fiber structure constituting an electrochemical element separator, due to the presence of a binder component containing a resin capable of forming a gel electrolyte on the main surface side having a small specific surface area, and the amount of the resin present on the main surface side having a small specific surface area, which is larger than the amount of the resin present on the main surface side having a large specific surface area, an electrolytic solution existing on the main surface side having a small specific surface area is absorbed and held by the resin, and the electrolytic solution existing on the main surface side having a small specific surface area is prevented from being attracted to the main surface side having a large surface area. Therefore, according to the present invention, it is possible to provide an electrochemical element separator capable of reducing the bias of the electrolytic solution that may occur in the electrochemical element separator and realizing an electrochemical element having more excellent electrical output characteristics.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a separator for an electrochemical element. [Background technology]

[0002] Conventionally, electrochemical elements have been required to have high thermal stability and low electrical resistance between electrodes so as to have excellent electrical output characteristics.

[0003] In order to realize a separator for electrochemical elements capable of providing an electrochemical element that satisfies this demand, the applicant of the present application has conducted research focusing on optimizing the pore size distribution in the separator for electrochemical elements. As a specific example, International Publication WO2019 / 017354 (Patent Document 1) proposes a separator for electrochemical elements in which the pore size distribution is optimized by adopting a laminated structure including a first fiber layer portion containing pulp-like fibers and a separate second fiber layer portion. In addition, in Examples 6 to 8 of Patent Document 1, a separator for electrochemical elements was prepared in which inorganic particles were supported by a polyacrylic acid resin binder on the second fiber layer side, with the aim of improving thermal stability. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] WO2019 / 017354 (claims, examples, 0087, etc.) Summary of the Invention [Problem to be solved by the invention]

[0005] However, as a result of continued research by the applicant, it was found that separators for electrochemical elements according to the conventional technology such as that disclosed in Patent Document 1 still have poor ion-permeability characteristics and high internal resistance, and therefore it is not always possible to provide an electrochemical element with excellent electrical output characteristics.

[0006] When the cause of this problem was investigated, it was thought that the following phenomenon occurred. In the separator for an electrochemical element according to the above-mentioned conventional technology, the first fiber layer portion has a large specific surface area due to the presence of pulp-like fibers with a small fiber diameter, and has a structure that easily holds an electrolyte. In comparison, the second fiber layer portion has a small specific surface area and has a structure that does not easily hold an electrolyte. Therefore, when an electrochemical element is prepared using a separator for an electrochemical element made of a fiber structure having a first fiber layer portion and a second fiber layer portion with such a structure, the electrolyte present on the main surface side (second fiber layer portion) of the fiber structure with a small specific surface area tends to be attracted to the main surface side (first fiber layer portion) with a large specific surface area.

[0007] As a result, the amount of electrolyte present on the main surface side of the fiber structure, which has a smaller specific surface area, is reduced, which is thought to cause an uneven distribution of electrolyte in the separator for electrochemical elements. Therefore, as long as the separator for electrochemical elements according to the conventional technology is used, the intended ion passing characteristics are not exhibited, the internal resistance is high, and it is thought to be difficult to provide an electrochemical element with excellent electric output characteristics. [Means for solving the problem]

[0008] The present invention relates to "A separator for an electrochemical element comprising a fiber structure, inorganic particles, and a binder component supporting the inorganic particles on one main surface of the fiber structure, a specific surface area of ​​the one principal surface of the fiber structure is smaller than a specific surface area of ​​the other principal surface of the fiber structure; The binder component Polyvinylidene fluoride resin Contains the amount of the resin present on the one main surface side is greater than the amount of the resin present on the other main surface side; Separators for electrochemical elements." It is. Effect of the Invention

[0009] As a result of investigations, the applicant of the present application has found that the above-mentioned problems can be solved by satisfying the configuration of the present invention in a separator for an electrochemical element "comprising a fiber structure, inorganic particles, and a binder component supporting the inorganic particles on one main surface of the fiber structure, wherein the specific surface area of ​​the one main surface of the fiber structure is smaller than the specific surface area of ​​the other main surface of the fiber structure." The reason for this is believed to be that the following effects are achieved.

[0010] The resin capable of forming the gel electrolyte is a resin capable of absorbing and retaining a known electrolytic solution used in preparing an electrochemical element, such as a resin capable of forming an electrolyte membrane of a fuel cell, etc. Therefore, it is considered that the presence of a binder component containing the resin on the main surface side with a small specific surface area in the fiber structure constituting the separator for an electrochemical element causes the electrolytic solution present on the main surface side with a small specific surface area to be absorbed and retained by the resin, and prevents the electrolytic solution present on the main surface side with a small specific surface area from being attracted to the main surface side with a large specific surface area.

[0011] In addition, in the fiber structure constituting the separator for electrochemical elements, the amount of the resin present on the main surface side with a smaller specific surface area is greater than the amount of the resin present on the main surface side with a larger specific surface area, so that a large amount of the resin capable of absorbing and retaining the electrolyte is present on the main surface side with a smaller specific surface area, which is considered to more effectively prevent the electrolyte present on the main surface side with a smaller specific surface area from being attracted to the main surface side with a larger specific surface area.

[0012] As described above, the present invention can prevent a decrease in the amount of electrolyte present on the main surface side having a small specific surface area in the fiber structure constituting the separator for electrochemical elements, thereby providing a separator for electrochemical elements that can reduce the uneven distribution of electrolyte in the separator for electrochemical elements and realize an electrochemical element with better electric output characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] In the present invention, various configurations, such as the following configurations, can be appropriately selected. Note that, unless otherwise specified, the various measurements described in the present invention were performed under atmospheric conditions of normal pressure and temperature of 25°C. Furthermore, unless otherwise specified, the various measurement results described in the present invention were measured to a value one digit smaller than the desired value, and the desired value was calculated by rounding off the value one digit smaller. As a specific example, when the desired value is to the first decimal place, the value was measured to the second decimal place, and the obtained value to the first decimal place was rounded off to calculate the value to the first decimal place, and this value was used as the desired value. Furthermore, each upper limit value and each lower limit value exemplified in the present invention can be arbitrarily combined.

[0014] In the separator for electrochemical elements according to the present invention, the fiber structure plays a role of forming the main skeleton of the separator for electrochemical elements. The fiber structure can be, for example, a fiber web or a nonwoven fabric, or a sheet-like fabric such as a woven fabric or a knitted fabric. In particular, when the fiber structure is a fiber web or a nonwoven fabric, it is preferable that the separator for electrochemical elements can be provided, since the porosity and the pore size are uniform, and therefore an electrochemical element having more excellent electric output characteristics can be realized.

[0015] The fiber structure may be composed of only one type of fabric, or may be composed of multiple and / or multiple types of fabrics laminated together. The lamination mode can be appropriately selected, and may be a mode in which the fabrics are simply laminated together, a mode in which the layers of the fabrics are integrated with an adhesive, a mode in which the constituent fibers of each fabric are integrated by entangling beyond the interlayer, a mode in which the constituent fibers of the fabrics are thermally melted to bond the fibers together and integrate the layers of the fabrics, a mode in which the layers of the fabrics are integrated by ultrasonic bonding, etc.

[0016] The constituent fibers of the fiber structure (hereinafter sometimes abbreviated as constituent fibers) are, for example, polyolefin resins (e.g., polyethylene, polypropylene, polymethylpentene, polyolefin resins having a structure in which a portion of the hydrocarbon is substituted with a nitrile group or a halogen such as fluorine or chlorine, etc.), styrene resins, polyvinyl alcohol resins, polyether resins (e.g., polyether ether ketone, polyacetal, modified polyphenylene ether, aromatic polyether ketone, etc.), polyester resins (e.g., polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polycarbonate, polyarylate, wholly aromatic polyester resins, etc.). ), polyimide resin, polyamideimide resin, polyamide resin (e.g., aromatic polyamide resin, aromatic polyetheramide resin, nylon resin, etc.), resin having a nitrile group (e.g., polyacrylonitrile, etc.), urethane resin, epoxy resin, polysulfone resin (e.g., polysulfone, polyethersulfone, etc.), fluorine resin (e.g., polytetrafluoroethylene, polyvinylidene fluoride, etc.), cellulose resin, polybenzimidazole resin, acrylic resin (e.g., polyacrylonitrile resin copolymerized with acrylic acid ester or methacrylic acid ester, modacrylic resin copolymerized with acrylonitrile and vinyl chloride or vinylidene chloride, etc.), etc., can be used. Note that these resins may be either linear or branched polymers, may be block copolymers or random copolymers, and may have any three-dimensional structure or crystallinity, and are not particularly limited. Furthermore, a mixture of multiple component resins may be used.

[0017] The constituent fibers may be made of one type of resin or a plurality of types of resin. Fibers made of a plurality of types of resin may be generally called composite fibers, such as core-sheath type, sea-island type, side-by-side type, orange type, bimetal type, and the like.

[0018] When the fiber structure contains heat-fusible fibers, the strength and shape stability can be improved by heat-fusible the constituent fibers. Such heat-fusible fibers may be fully fusible heat-fusible fibers, or may be partially fusible heat-fusible fibers such as the above-mentioned composite fibers. As a component (resin) that exhibits heat fusibility in the heat-fusible fibers, for example, heat-fusible fibers containing low-melting point polyolefin resins or low-melting point polyester resins can be appropriately selected and used.

[0019] These constituent fibers may include irregular cross-section fibers other than the roughly circular and elliptical fibers. The irregular cross-section fibers may have a fiber cross section of a hollow shape, a polygonal shape such as a triangular shape, an alphabetic shape such as a Y-shape, an irregular shape, a multi-lobed shape, a symbolic shape such as an asterisk shape, or a shape in which a plurality of these shapes are combined.

[0020] The constituent fibers may also include pulp-like fibers in which numerous fine fibers (fibrils) are generated from a single fiber by mechanical shearing force or the like. Since pulp-like fibers have a large surface area, fabrics containing the pulp-like fibers tend to have a dense structure. As a result, a fiber structure containing pulp-like fibers as constituent fibers has uniform and dense pore size, which is preferable because it can provide a separator for electrochemical elements that can realize electrochemical elements with superior electrical output characteristics.

[0021] The freeness of the pulp-like fiber can be adjusted as appropriate, but the smaller the freeness, the denser the fiber structure becomes, and there is a tendency that an electrochemical element separator capable of realizing an electrochemical element having superior electric output characteristics can be provided. Therefore, the freeness of the pulp-like fiber is preferably 500 ml CSF or less, more preferably 400 ml CSF or less, and more preferably 300 ml CSF or less. On the other hand, the lower limit of the freeness of the pulp-like fiber is appropriately selected, but it is practical to set it to 0.1 ml CSF or more. In the present invention, the "freeness" refers to a value measured using a JIS P8121 Canadian Standard Freeness Tester.

[0022] The pulp-like fibers can be fibers containing the above-mentioned known resins, but pulp-like fibers of aramid resin, polyolefin resin, acrylic resin, liquid crystal polyester resin, etc. are preferred because they are easy to provide a separator for electrochemical elements with low moisture content. Furthermore, it is preferred that the constituent fibers contain pulp-like fibers of aramid resin because they have high strength and are therefore less likely to short circuit and have excellent heat resistance. The fiber structure may contain one type of pulp-like fiber or multiple types of pulp-like fibers.

[0023] The fineness of the constituent fibers other than pulp-like fibers in which no fibrils are generated (hereinafter, sometimes referred to as staple fibers) is not particularly limited, but in order to realize a separator for electrochemical devices having a uniform and dense pore size, it is preferably 5d or less, more preferably 2d or less, and more preferably 1d or less. On the other hand, the lower limit of the fineness is appropriately selected, but it is practical to set it to 0.01d or more.

[0024] The fiber length of the constituent fibers is not particularly limited, but in order to realize a separator for electrochemical elements with uniform and dense pore size, it is preferably 20 mm or less, which is called short fiber, more preferably 15 mm or less, and more preferably 10 mm or less. On the other hand, the lower limit of the fiber length is appropriately selected, but it is practical to set it to 0.5 mm or more. The "fiber length" refers to a value measured in accordance with JIS L1015 (2010), 8.4.1c) direct method (C method).

[0025] The constituent fibers can be obtained by known methods such as melt spinning, dry spinning, wet spinning, direct spinning (melt blowing, spunbonding, electrostatic spinning, etc.), a method of extracting fibers having a small fiber diameter by removing one or more resin components from composite fibers, and a method of beating fibers to obtain split fibers.

[0026] The fiber web or nonwoven fabric can be prepared, for example, by a dry method in which the above-mentioned fibers are fed into a carding device or an air-laying device to entangle the fibers; a wet method in which the fibers are dispersed in a solvent and laid into a sheet to entangle the fibers; or a method in which the fibers are spun and collected using a direct spinning method (such as a melt-blowing method, a spunbonding method, an electrostatic spinning method, or a method in which a spinning solution and a gas flow are discharged in parallel to spin the fibers (e.g., the method disclosed in JP-A-2009-287138), etc.).

[0027] A nonwoven fabric can be prepared by entangling and / or integrating the constituent fibers of the prepared fiber web. Examples of methods for entangling and / or integrating the constituent fibers include a method of entangling with needles or water flow, and a method of subjecting the fiber web to heat treatment, etc., and bonding or fusing the constituent fibers together with an adhesive or adhesive fiber. The heat treatment method can be appropriately selected, and examples of the heat treatment method include a method of heating or heating and pressurizing with a roll, a method of heating by subjecting the web to a heater such as an oven dryer, a far-infrared heater, a dry heat dryer, or a hot air dryer, and a method of irradiating infrared rays without pressure to heat the resin contained therein.

[0028] However, in order to prevent the openings of the fiber structure from being unintentionally blocked by the adhesive, the fiber structure is preferably one in which the constituent fibers are bonded together by fiber bonding. In order to prepare a fiber structure having fiber-bonded constituent fibers, it is preferable that the constituent fibers include adhesive fibers. Specific examples of adhesive fibers include composite fibers such as core-sheath fibers and side-by-side fibers made of a high melting point resin and a low melting point resin, or undrawn fibers made only of a resin that melts or softens at a temperature lower than the melting point or softening point of the other fibers. By bonding the constituent fibers with adhesive fibers, it is possible to provide a separator for an electrochemical element that is less likely to short-circuit due to the improved strength. When the fabric is a woven or knitted fabric, the woven or knitted fabric can be prepared by weaving or knitting the fibers prepared as described above.

[0029] In addition to the fiber web, fabrics such as nonwoven fabrics, woven fabrics, and knitted fabrics may also be subjected to the above-mentioned method of entangling and / or integrating the constituent fibers.

[0030] Since the uniform and dense pore size makes it easy to provide a separator for an electrochemical element that can realize an electrochemical element with superior electrical output characteristics, the fiber structure of the present invention is preferably a laminated nonwoven fabric formed by laminating a first fiber layer portion containing pulp-like fibers and a second fiber layer portion containing staple fibers in an amount of more than 50 mass % of the constituent fibers of the second fiber layer portion.

[0031] In addition, in a fiber structure having the above-mentioned configuration, the specific surface area of ​​the main surface of the fiber structure where the second fiber layer portion is exposed is likely to be smaller than the specific surface area of ​​the main surface of the fiber structure where the first fiber layer portion is exposed. Therefore, a fiber structure having such a configuration is likely to become the fiber structure according to the present invention.

[0032] The term "principal surface" as used herein refers to a broad surface of a fabric or fiber structure. Specifically, in the present invention, one broad surface of a fiber structure is referred to as one principal surface, and the principal surface of the fiber structure on the opposite side to the principal surface is referred to as the other principal surface.

[0033] When the fiber structure has a structure in which some of the constituent fibers (e.g., pulp-like fibers) of the first fiber layer portion penetrate into the second fiber layer portion, the first fiber layer portion is effectively reinforced by the second fiber layer portion as a result of the two layers being firmly integrated, and this is preferable because it allows the provision of a separator for electrochemical elements that can provide electrochemical elements that are less likely to short-circuit.

[0034] When observing a cross section in the thickness direction of a fiber structure having a first fiber layer portion and a second fiber layer portion, if some of the constituent fibers of the first fiber layer portion are present within the second fiber layer portion (for example, if the constituent fibers of the first fiber layer portion (e.g., pulp-like fibers) cross the boundary between the first fiber layer portion and the second fiber layer portion and penetrate from the first fiber layer portion into the second fiber layer portion), it can be determined that the fiber structure is one in which some of the constituent fibers of the first fiber layer portion have penetrated into the second fiber layer portion.

[0035] In particular, it is preferable that some of the constituent fibers (e.g., pulp-like fibers) of the first fiber layer portion penetrate deep enough to be exposed on the main surface of the fiber structure on the side of the second fiber layer portion, in order to provide a separator for electrochemical elements that can provide electrochemical elements that are less likely to short-circuit.

[0036] In addition, when the first fiber layer portion includes pulp-like fibers as the constituent fibers, it is preferable that the first fiber layer portion includes short staple fibers as the other constituent fibers. The structure in which the pulp-like fibers and short staple fibers are entangled improves the strength compared to a structure including only pulp-like fibers as the constituent fibers, and the presence of the short staple fibers prevents the portions protruding from the electrode surface from penetrating the separator for electrochemical devices when stacked or wound with the electrodes, which is preferable as a separator for electrochemical devices that can provide an electrochemical device that is less likely to short-circuit.

[0037] When the first fiber layer portion contains pulp-like fibers, the higher the mass percentage of the pulp-like fibers in the fibers constituting the first fiber layer portion, the denser the first fiber layer portion becomes, and the more likely it is that a separator for an electrochemical element can be provided that can realize an electrochemical element with excellent electrical output characteristics such as excellent high-rate discharge. Therefore, the mass percentage of the pulp-like fibers in the fibers constituting the first fiber layer portion is preferably 10 mass% or more, more preferably 20 mass% or more, and even more preferably 50 mass% or more. The upper limit is adjusted as appropriate, but is 100 mass% or less, can be 95 mass% or less, and can be 90 mass% or less.

[0038] The basis weight of the fiber structure is appropriately selected, but is preferably 1 to 50 g / m 2 and 2 to 40 g / m 2 and 3 to 30 g / m 2 It can be.

[0039] The thickness of the fiber structure is appropriately selected, but the thickness is preferably 150 μm or less, more preferably 100 μm or less, and more preferably 50 μm or less so that the separator for electrochemical elements can provide an electrochemical element with low internal resistance due to its thin thickness. On the other hand, if the thickness is too thin, the strength decreases and the separator for electrochemical elements may be easily cracked, so that the thickness is realistically 5 μm or more. In the present invention, the "thickness" refers to the arithmetic average value of measurements performed at 10 randomly selected points under a load of 5 N using an outside micrometer (0 to 25 mm) as specified in JIS B7502:1994.

[0040] In the fiber structure of the present invention, the specific surface area of ​​one of the main surfaces is smaller than the specific surface area of ​​the other main surface. Note that the "specific surface area" in the present invention refers to the specific surface area of ​​a measurement object having a main surface to be measured, which is measured by treating the measurement object in a vacuum at a temperature of 70°C for 4 hours, and then cooling to room temperature to obtain a specific surface area of ​​1×10 -3 After evacuation to Torr, about 0.5 g of a sample was taken from the portion constituting the main surface of the measurement object, and the sample was placed in a gas adsorption measuring device [BELSORP28A, manufactured by BEL Japan Co., Ltd.] and measured by the BET method. Krypton was used as the adsorption gas.

[0041] Specifically, the specific surface area of ​​one main surface of the fiber structure is determined by measuring the specific surface area of ​​a sample taken from one main surface of the fiber structure, and the specific surface area of ​​the other main surface of the fiber structure is determined by measuring the specific surface area of ​​a sample taken from the other main surface of the fiber structure.

[0042] Pulp-like fibers have a larger surface area than staple fibers, and therefore, when the ratio of pulp-like fibers (e.g., the number of fibers or the weight ratio) in the fiber composition constituting one main surface of a fiber structure is smaller than the ratio of pulp-like fibers (e.g., the number of fibers or the weight ratio) in the fiber composition constituting the other main surface, the specific surface area of ​​one main surface of the fiber structure will be smaller than the specific surface area of ​​the other main surface.

[0043] The fiber composition of one main surface of a fiber structure and the fiber composition of the other main surface can be confirmed and compared using electron microscope photographs of both main surfaces of the fiber structure.

[0044] In the separator for electrochemical elements according to the present invention, the inorganic particles play a role in improving the thermal stability of the separator for electrochemical elements. Furthermore, the pore size on the side of the fiber structure where the inorganic particles are present can be made uniform and dense, and the electrolyte (and the resin capable of forming a gel electrolyte that absorbs and retains the electrolyte) can be present between the inorganic particles. In other words, the inorganic particles also play a role in increasing the amount of electrolyte that can be present on the side of the fiber structure where the inorganic particles are present. Therefore, by using a separator for electrochemical elements that includes inorganic particles, it is possible to realize an electrochemical element with better electric output characteristics.

[0045] The type of inorganic particles constituting the separator for electrochemical elements of the present invention can be appropriately selected. For example, oxides such as iron oxide, SiO2 (silica), Al2O3 (alumina), alumina-silica composite oxide, TiO2, SnO2, BaTiO2, ZrO2, tin-indium oxide (ITO), lithium titanate (LTO), etc.; nitrides such as aluminum nitride and silicon nitride; poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate; covalent crystals such as silicon and diamond; clays such as talc and montmorillonite; mineral resource-derived substances or their artificial products such as boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, and oxides of inorganic components such as metal oxides can be exemplified. Furthermore, as disclosed in International Publication No. 2009 / 066916 (JP 2011-503828 A), electrode active material particles that undergo electrochemical oxidation and reduction reactions (e.g., anode active material particles selected from the group consisting of natural graphite, artificial graphite, carbonaceous material, lithium titanate (LTO), silicon (Si), tin (Sn), or mixtures thereof) may be used.

[0046] The average particle diameter (D 50 The "average particle diameter of primary particles (D)" is adjusted as appropriate depending on the type of inorganic particles and the performance and characteristics required for the separator for electrochemical devices, but can be 10 μm or less, 8 μm or less, or 5 μm or less. The lower limit can be adjusted as appropriate, but it is practical to set it to 50 nm or more. 50 "D" refers to a value calculated from particle size measurement data obtained from the scattering intensity obtained by continuous measurement for 3 minutes using a dynamic light scattering method with an FPRA1000 (measurement range 3 nm to 5000 nm) manufactured by Otsuka Electronics Co., Ltd. More specifically, particle size measurements were performed five times, the particle size measurement data obtained from the measurements were arranged in order of narrowest particle size distribution width, and the particle size at the 50% point of the cumulative value of the particle in the particle size measurement data showing the third narrowest particle size distribution width was determined as the average particle size of primary particles (hereinafter, D 50The temperature of the measurement solution used in the measurement is adjusted to 25°C, and pure water at 25°C is used as a blank for measuring scattering intensity. When the particle size of the particles to be measured is listed on a web page or in a catalog by the manufacturer or trading company, the particle size is referred to as the average particle size of the primary particles (D 50 ) can be regarded as

[0047] The mass of the inorganic particles supported on the fiber structure is not particularly limited, but is preferably 0.1 g / m 2 It can be more than 0.5g / m 2 It can be more than 1 g / m 2 On the other hand, the upper limit of the supported mass can be appropriately adjusted, but is not more than 20 g / m 2 The following is realistic.

[0048] A separator for an electrochemical element including the fiber structure carrying inorganic particles as described above tends to have a small maximum pore size and a small minimum pore size and a narrow pore size distribution, and therefore it is possible to provide a separator for an electrochemical element that can realize an electrochemical element having more excellent electric output characteristics.

[0049] In the separator for electrochemical elements according to the present invention, the binder component plays a role of supporting inorganic particles on the main surface of the fiber structure. The inorganic particles supported by the binder component are not limited to those present only on one of the main surfaces of the fiber structure, and may also be present in the main surface and in voids between the fibers constituting the fiber structure via the binder component.

[0050] Furthermore, in addition to one main surface of the fiber structure, the inorganic particles may be supported by the binder component on the other main surface of the fiber structure.

[0051] The binder component according to the present invention contains a resin capable of forming a gel electrolyte. In the present invention, the term "resin capable of forming a gel electrolyte" expresses the characteristics of the resin, and refers to a resin capable of absorbing and retaining a known electrolytic solution used in preparing an electrochemical element, such as a resin capable of forming an electrolyte membrane of a fuel cell. The type of resin capable of forming a gel electrolyte can be appropriately selected, and examples thereof include polyvinylidene fluoride resin, polyethylene oxide resin, polyacrylonitrile resin, and polymethyl methacrylate resin.

[0052] The polyvinylidene fluoride resin in the present invention refers to a polymer having a -(CH2CF2)- structure in its structure. It may be a homopolymer in which the structure is continuously constituted, or a copolymer obtained by copolymerization with other structures. Hereinafter, the polyvinylidene fluoride resin may be referred to as PVDF. As PVDF, for example, PVDF-HFP (copolymer resin with HFP structure), PVDF-CTFE (copolymer resin with CTFE structure), PVDF homopolymer, etc. can be used.

[0053] The molecular weight of PVDF can be appropriately selected, and PVDF with a molecular weight higher than 380,000 can be used, PVDF with a molecular weight of 570,000 or more can be used, and PVDF with a molecular weight of 750,000 or more can be used. The molecular weight in the present invention is a value measured based on gel permeation chromatography. When the molecular weight of the resin used is described in a catalog or paper, the molecular weight is regarded as the molecular weight of the resin.

[0054] PVDF has excellent heat resistance, for example, a higher softening temperature than polyethylene oxide resins. Therefore, by including PVDF in the binder component, it is possible to provide a separator for an electrochemical element that is highly thermally stable and difficult to short-circuit. In addition, even in a heated atmosphere during the manufacturing process of the separator for an electrochemical element, it is difficult for the separator to unintentionally soften or melt, and therefore PVDF is unlikely to be present in a coating form on the main surface. Therefore, it is possible to provide a separator for an electrochemical element that can prevent the air permeability of the separator for an electrochemical element from decreasing and realize an electrochemical element with better electric output characteristics. The binder component may contain one or more types of PVDF.

[0055] The polyethylene oxide resin (hereinafter sometimes abbreviated as PEO) in the present invention refers to a polymer having a -(CH2CH2O)- structure in its structure. It may be a homopolymer in which the structure is continuously constituted, or a copolymer obtained by copolymerizing with other structures. The molecular weight of PEO can be appropriately selected, and PEO having a molecular weight higher than 380,000 can be used, PEO having a molecular weight of 570,000 or more can be used, and PEO having a molecular weight of 750,000 or more can be used.

[0056] The polyacrylonitrile resin in the present invention refers to a polymer having a -(CH2CHCN)- structure in its structure. It may be a homopolymer in which the structure is continuously formed, or a copolymer obtained by copolymerizing with other structures. The molecular weight of the polyacrylonitrile resin can be appropriately selected, and a polyacrylonitrile resin having a molecular weight of more than 380,000 can be used, a polyacrylonitrile resin having a molecular weight of 570,000 or more can be used, or a polyacrylonitrile resin having a molecular weight of 750,000 or more can be used.

[0057] The polymethyl methacrylate resin in the present invention refers to a polymer having a -(CH2C(COOCH3)CH3)- structure in its structure. It may be a homopolymer in which the structure is continuously formed, or a copolymer obtained by copolymerizing with other structures. The molecular weight of the polymethyl methacrylate resin can be appropriately selected, and a polymethyl methacrylate resin having a molecular weight of more than 380,000 can be used, a polymethyl methacrylate resin having a molecular weight of 570,000 or more can be used, and a polymethyl methacrylate resin having a molecular weight of 750,000 or more can be used.

[0058] The type of resin capable of forming the gel electrolyte contained in the binder component may be one or more types. However, it is preferable to adopt PVDF and / or PEO as the resin capable of forming the gel electrolyte because of its excellent function of absorbing and retaining the electrolytic solution, and it is more preferable to adopt PVDF as the resin capable of forming the gel electrolyte because of its excellent heat resistance. In particular, it is preferable to adopt only PVDF as the resin capable of forming the gel electrolyte.

[0059] The ratio of the resin capable of forming a gel electrolyte contained in the binder component can be adjusted as appropriate, but in order to effectively exert the effect of providing a separator for an electrochemical element that can prevent a decrease in the amount of electrolyte present on the main surface side with a smaller specific surface area, as described below, and can realize an electrochemical element with excellent electric output characteristics such as excellent high-rate discharge, the binder component is preferably composed only of a resin capable of forming a gel electrolyte. The mass of the binder component that supports the inorganic particles on the fiber structure can be adjusted as appropriate, but is preferably 0.001 to 20 g / m 2 and can be 0.005 to 15 g / m 2 and the thickness can be 0.01 to 10 g / m 2 It can be.

[0060] By applying a binder component containing a resin capable of forming a gel electrolyte to one of the principal surfaces of the fiber structure, a separator for electrochemical elements can be prepared that includes a fiber structure in which the amount of the resin present on the principal surface to which the binder component is applied is greater than the amount of the resin present on the other principal surface. The amount of the resin present on one principal surface of the fiber structure and the amount of the resin present on the other principal surface can be confirmed and compared using electron microscope photographs of both principal surfaces of the fiber structure.

[0061] The various configurations of the separator for electrochemical elements, such as thickness, basis weight, and porosity, are appropriately adjusted so as to realize an electrochemical element having excellent electric output characteristics, such as excellent high-rate discharge. 2 and 8 to 45 g / m 2and 10 to 40 g / m 2 The thickness can be 8 to 100 μm, 9 to 60 μm, or 10 to 30 μm. The porosity can be 20% or more, 30% or more, or 40% or more.

[0062] In the present invention, the "void ratio (P)" (unit: %) refers to a value obtained from the following formula. P = 100‐(Fr1 + Fr2 + + Frn) Here, Frn indicates the packing rate (unit: %) of each component n constituting the separator for electrochemical elements, and is the value obtained from the following formula. Frn = {(M × Prn) / (T × SGn)} × 100 Here, M is the basis weight of the separator for electrochemical elements (unit: g / cm 2 ), T is the thickness of the separator for electrochemical elements (unit: cm), Prn is the abundance mass ratio of various components n contained in the separator for electrochemical elements, and SGn is the specific gravity of various components n (unit: g / cm 3 ) respectively.

[0063] Next, a method for producing a separator for an electrochemical element according to the present invention will be described by way of an example, with the explanation being omitted for the same configuration as that described above.

[0064] The method for producing the separator for an electrochemical element can be appropriately selected. As an example, (1) preparing a fabric containing staple fibers as constituent fibers; (2) A step of forming a first fiber layer portion containing pulp-like fibers on one main surface of the fabric by papermaking a papermaking liquid containing pulp-like fibers so that a portion of the pulp-like fibers penetrates into the fabric; (3) removing the dispersion medium of the papermaking solution from a laminate having the first fiber layer portion on one main surface of the fabric to prepare a fiber structure; (4) applying a dispersion liquid containing a binder component containing a resin capable of forming a gel electrolyte and inorganic particles to a principal surface of the fiber structure having a smaller specific surface area (a principal surface derived from the fabric); (5) removing the dispersion medium from the fiber structure to which the dispersion has been applied; It is possible to use a method for producing a separator for an electrochemical element comprising the steps of:

[0065] In step (2), the dispersion medium of the papermaking solution containing pulp-like fibers can be appropriately selected from well-known ones such as water, and a dispersion medium containing a dispersant and / or an activator can be used. The papermaking solution is poured onto one main surface of the cloth and papered up, and at that time, a suction device may be provided on the other main surface of the cloth to suck and remove the dispersion medium.

[0066] In step (3), a method for removing the dispersion medium from the laminate is appropriately selected, and examples of methods that can be used include a method for removing the dispersion medium by sucking or blowing it away from the laminate, a method for removing the dispersion medium from the laminate by subjecting it to the above-mentioned heating machine, a method for removing the dispersion medium from the laminate by leaving it in a room temperature environment or a reduced pressure environment, a method for removing the dispersion medium from the laminate by making a water-absorbent fabric such as felt absorb the dispersion medium, etc. If the laminate has an adhesive component such as an adhesive or adhesive fiber, the adhesive component may be melted by subjecting it to a heating machine in this step to bond the fibers together.

[0067] In step (4), the dispersion medium of the dispersion liquid can be appropriately selected from known ones such as water. The existence mode of the binder component in the dispersion liquid can be appropriately selected, and it may be dissolved in the dispersion medium or may be dispersed in the dispersion medium in a particulate form. The method of applying the dispersion liquid to the main surface of the fiber structure having a small specific surface area can be appropriately selected, and a method of spraying the dispersion liquid on the main surface, a method of applying the dispersion liquid to the main surface using a coating method such as a kiss coater method using a gravure roll, etc. can be adopted.

[0068] In step (5), the method for removing the dispersion medium from the laminate can be appropriately selected, and the method described in step (3) can be adopted. In particular, the method of subjecting the laminate to the heater described above is adopted, and the binder component is softened, melted, or crosslinked by heat treatment with the heater, so that the binder component can support inorganic particles on one main surface of the fiber structure. The heating temperature at this time is appropriately adjusted, but can be 80°C or higher. The upper limit of the heating temperature is appropriately adjusted, but it is preferably 150°C or lower to prevent unintentional melting or softening of the constituent fibers, etc.

[0069] An electrochemical element can be prepared by using the separator for an electrochemical element thus prepared as it is, but if necessary, an additional member such as a reinforcing layer may be provided on the separator for an electrochemical element to prepare an electrochemical element.

[0070] The fiber structure or the separator for an electrochemical device may be subjected to a hydrophilization treatment step in order to impart or improve the electrolyte retention. Examples of the hydrophilization treatment step include sulfonation treatment, fluorine gas treatment, graft polymerization treatment with a vinyl monomer, surfactant treatment, discharge treatment, and hydrophilic resin imparting treatment.

[0071] Furthermore, the separator for an electrochemical device may be subjected to various secondary processes, such as punching out a shape that matches the shape of an electrochemical device to be used, or processing so that it can assume a wound shape. EXAMPLES

[0072] The present invention will be described in detail below with reference to examples, but the scope of the present invention is not limited to these examples. Various measurement methods were performed as follows.

[0073] (Method of measuring tensile strength and tensile elongation) A test piece (shape: rectangular, length: 200 mm, width: 50 mm) was taken from the separator for electrochemical elements so that the machine direction (flow direction during manufacturing) and the length direction were aligned. The test piece was then subjected to a constant-speed extension tensile tester (Orientec Co., Ltd., Tensilon, initial gripping distance: 100 mm, tensile speed: 300 mm / min), and the tensile strength (N / 50 mm) was calculated from the strength when the sample piece was pulled until it broke.

[0074] In addition, the tensile elongation (%) of the test piece was calculated by substituting the gripping distance (mm) at the maximum load measured when the test piece was pulled until it broke into the following formula.

[0075] a = {(b-c) / c} × 100 a: Tensile elongation (%) b: Grip spacing at maximum load (mm) c: Initial gripping distance (100 mm)

[0076] (Method of measuring Gurley value) A test piece was taken from the separator for electrochemical elements, and subjected to the method specified in "JIS P8117:2009 (Paper and paperboard -- Air permeability and air resistance test method (intermediate range) -- Gurley method) a) Gurley tester method," to calculate the Gurley value (sec / 100cc). Generally, the lower the Gurley value of a separator for electrochemical elements, the better the ion-permeability characteristics and the lower the internal resistance, which means that the separator for electrochemical elements can provide a lithium ion secondary battery with excellent electrical output characteristics.

[0077] (Method of measuring 12C discharge capacity) (1) Creating the positive electrode 87 parts by mass of lithium cobalt oxide powder, 6 parts by mass of acetylene black, and 7 parts by mass of polyvinylidene fluoride were dissolved in N-methyl-pyrrolidone to prepare a positive electrode paste with a polyvinylidene fluoride concentration of 13% by mass. This paste was then applied to an aluminum foil with a thickness of 20 μm, dried, and pressed to prepare a positive electrode with a thickness of 90 μm. (2) Creating the negative electrode As the negative electrode active material, 90 parts by mass of natural graphite powder and 10 parts by mass of polyvinylidene fluoride were dissolved in N-methyl-pyrrolidone to prepare a negative electrode paste with a polyvinylidene fluoride concentration of 13% by mass. This paste was applied onto a copper foil with a thickness of 15 μm, dried, and pressed to prepare a negative electrode with a thickness of 70 μm. (3) Preparation of non-aqueous electrolyte As a non-aqueous electrolyte, a 1 mol / L solution (Kishida Chemical Co., Ltd.) in which LiPF6 was dissolved in a mixed solvent of ethylene carbonate and diethyl carbonate (ratio = 50 mass %:50 mass %) was prepared. (4) Fabrication of lithium-ion secondary batteries A negative electrode (diameter: 12 mm), a separator for electrochemical elements (diameter: 16 mm, inorganic particle-coated side facing the positive electrode), and a positive electrode (diameter: 12 mm) were stacked in this order in a coin-shaped cell, and then a non-aqueous electrolyte was poured into each of them to prepare a lithium-ion secondary battery. The mass ratio of the positive electrode to the negative electrode was 1:1.1. As described above, three of each type of lithium-ion secondary battery was prepared using the separator for electrochemical elements. When the capacity of each of the fabricated lithium ion secondary batteries is represented as C, the batteries were charged to 4.2 V at a charge rate of 0.2 C, left for 15 minutes, and then discharged at a discharge rate of 12 C until the voltage reached 3.0 V. At this time, the discharge capacity of each lithium ion secondary battery at a discharge rate of 12 C was measured. This measurement was performed on three lithium ion secondary batteries each, and the arithmetic average value of the obtained values ​​was calculated to obtain the discharge capacity (mAh). It should be noted that the higher the discharge capacity of a separator for electrochemical elements, the more excellent the electric output characteristics of a lithium ion secondary battery can be provided by the separator for electrochemical elements.

[0078] (Preparation of fiber structures 1 and 2) A fiber web obtained by wet-laid papermaking of polyethylene terephthalate short fibers (fiber length: 3 mm, fineness: 0.2 d) is heated and pressurized by passing it through a heat roll with a surface temperature adjusted to 180°C, whereby the polyethylene terephthalate short fibers are crystallized and the polyethylene terephthalate short fibers are bonded to each other without melting, to form a wet-laid nonwoven fabric (thickness: 10 μm, basis weight: 5.5 g / m 2 ) was prepared. Next, a papermaking solution was prepared containing polyethylene terephthalate short fibers (fiber length: 3 mm, fineness: 0.2 d) and aramid resin pulp-like fibers (freeness: 50 ml CSF) in a ratio of polyethylene terephthalate short fibers:aramid resin pulp-like fibers = 20 mass%:80 mass%. Then, after the papermaking liquid was laid down on one main surface of the wetlaid nonwoven fabric, the dispersion medium contained in the papermaking liquid was removed by suction from the main surface of the wetlaid nonwoven fabric opposite to the side where the papermaking liquid was laid down, thereby preparing a laminated web having a fiber deposition layer composed of a mixture of polyethylene terephthalate short fibers and aramid resin pulp-like fibers on one main surface of the wetlaid nonwoven fabric. Next, the laminated web was subjected to a heat treatment by exposing it to an atmosphere at a temperature of 145°C, and the residual dispersion medium was removed from the laminated web and it was then dried. Thereafter, the polyethylene terephthalate short fibers were crystallized by heating and pressing using a heat roll with a surface temperature adjusted to 180°C, and the polyethylene terephthalate short fibers were bonded to each other and to the pulp-like fibers of the aramid resin without melting, to obtain a fiber structure 1 (thickness: 18 μm, basis weight: 10.5 g / m 2 ) was prepared.

[0079] In addition, a fiber structure 2 (thickness: 20 μm, basis weight: 8.5 g / m) was prepared in the same manner, except that the amount of papermaking liquid applied to one main surface of the wetlaid nonwoven fabric was reduced. 2 ) was prepared.

[0080] In each of the fiber structures prepared as described above, a portion of the short fibers and / or pulp-like fibers constituting the fiber deposition layer was deeply embedded in the fiber layer derived from the wetlaid nonwoven fabric until it was exposed on the main surface (main surface A) where the fiber layer derived from the wetlaid nonwoven fabric was exposed. In each of the fiber structures, the specific surface area of ​​the main surface (main surface A) opposite to the side where the papermaking liquid was laid up in the wetlaid nonwoven fabric was smaller than the specific surface area of ​​the other main surface of the fiber structure.

[0081] (Preparation of Dispersions 1 to 4) Silica particles (D 50 A dispersion liquid 1 to 4 (liquid temperature: 25° C., solid content concentration: 27% by mass) was prepared by adding a particulate binder component after mixing and continuing to stir the mixture. The solid mass composition of the dispersion was as follows: Dispersion liquid 1: Silica particles: 97 parts by weight, polyacrylic acid resin: 3 parts by weight Dispersion liquid 2: Silica particles: 97 parts by mass, PVDF: 3 parts by mass Dispersion liquid 3: Silica particles: 92 parts by weight, PVDF: 8 parts by weight Dispersion liquid 4: Silica particles: 92 parts by mass, PEO: 8 parts by mass The details of each binder component are as follows: Polyacrylic acid resin: Not a resin that can form a gel electrolyte. ·PVDF: A copolymer of polyvinylidene fluoride and acrylic, a resin that can form a gel electrolyte. PEO: A homopolymer of polyethylene oxide, a resin that can form a gel electrolyte.

[0082] Comparative Example 1 Dispersion liquid 1 was applied to the main surface A of the fiber structure 1 using a gravure roll. Then, the dispersion medium of the dispersion liquid was removed by a dryer, and silica particles were supported on one of the main surfaces of the fiber structure by the binder component, thereby preparing a separator for electrochemical devices.

[0083] Example 1 A separator for an electrochemical element was prepared in the same manner as in Comparative Example 1, except that Dispersion Liquid 2 was used, in which silica particles were supported on one main surface of a fiber structure by the binder component.

[0084] (Examples 2 to 3) A separator for an electrochemical element in which silica particles were supported on one main surface of a fiber structure by the binder component was prepared in the same manner as in Example 1, except that the amount of the dispersion applied was reduced.

[0085] In addition, in all of the electrochemical element separators prepared, the amount of silica particles and binder components present on one main surface side (main surface A side) of the fiber structure was greater than the amount of silica particles and binder components present on the other main surface side.

[0086] Various physical properties of the separator for electrochemical elements prepared as described above were measured and are summarized in Table 1. Note that components that were not provided are marked with "-" in the table.

[0087] [Table 1]

[0088] From the results of comparing Comparative Example 1 and Example 1, it was found that by using a resin capable of forming a gel electrolyte as a binder component, electrochemistry with a high 12C discharge capacity can be realized. In addition, it was found that all of the separators for electrochemical elements prepared in Examples 1 to 3 can realize electrochemistry with a high 12C discharge capacity.

[0089] (Examples 4 to 7) Dispersion liquid 2 was applied to the main surface A of the fiber structure 2 using a gravure roll. Thereafter, the dispersion medium of the dispersion liquid was removed by a dryer, and silica particles were supported on one of the main surfaces of the fiber structure by the binder component, thereby preparing a separator for electrochemical devices. In each example, the amount of the dispersion liquid applied was changed.

[0090] In all of the electrochemical element separators prepared, the amount of silica particles and binder components present on one main surface side (main surface A side) of the fiber structure was greater than the amount of silica particles and binder components present on the other main surface side.

[0091] Various physical properties of the separator for electrochemical elements prepared as described above were measured and are summarized in Table 2. Note that components that were not provided are marked with "-" in the table.

[0092] [Table 2]

[0093] It was found that all of the separators for electrochemical elements prepared in Examples 4 to 7 were capable of achieving electrochemistry with a high 12C discharge capacity.

[0094] Example 8 Dispersion liquid 3 was applied to the main surface A of the fiber structure 2 using a gravure roll. Thereafter, the dispersion medium of the dispersion liquid was removed by a dryer, and silica particles were supported on one of the main surfaces of the fiber structure by the binder component, thereby preparing a separator for electrochemical devices.

[0095] Example 9 Dispersion liquid 4 was applied to the main surface A of the fiber structure 2 using a gravure roll. Thereafter, the dispersion medium of the dispersion liquid was removed by a dryer, and silica particles were supported on one of the main surfaces of the fiber structure by the binder component, thereby preparing a separator for electrochemical devices.

[0096] Example 10 Dispersion liquid 4 was applied to the main surface A of the fiber structure 1 using a gravure roll. Thereafter, the dispersion medium of the dispersion liquid was removed by a dryer, and silica particles were supported on one of the main surfaces of the fiber structure by the binder component, thereby preparing a separator for electrochemical devices.

[0097] In all of the electrochemical element separators prepared, the amount of silica particles and binder components present on one main surface side (main surface A side) of the fiber structure was greater than the amount of silica particles and binder components present on the other main surface side.

[0098] Various physical properties of the separator for electrochemical elements prepared as described above were measured and are summarized in Table 3. Note that components that were not provided are marked with "-" in the table.

[0099] [Table 3]

[0100] It was found that all of the prepared separators for electrochemical elements of Examples 8 to 10 were capable of achieving electrochemistry with a high 12C discharge capacity.

[0101] However, when the main surface (main surface derived from main surface A) of the separators for electrochemical elements prepared in Examples 8 to 10 on the side to which the dispersion liquid was applied was checked, PEO was present in the form of a coating on the main surface in Example 9 (and also in Example 10). On the other hand, PVDF was not present in the form of a coating on the main surface in Example 8. Therefore, the separator for electrochemical elements in Example 9 had a lower Gurley value than the separator for electrochemical elements in Example 8, which was thought to be the cause of the decrease in 12C discharge capacity. The reason for this problem is believed to be that PEO has poor heat resistance and unintentionally softens or melts in a heated atmosphere, causing it to deform into a film. From this point of view, it was found that by using PVDF, which has excellent heat resistance, as a binder component, it is possible to realize electrochemistry with excellent electrical output characteristics, such as a higher 12C discharge capacity.

[0102] From the above, it was found that the separator for an electrochemical element according to the present invention can provide an electrochemical element having excellent electric output characteristics. [Industrial Applicability]

[0103] The separator for electrochemical elements of the present invention can be used as a separator for electrochemical elements that separates electrodes in electrochemical elements such as primary batteries (e.g., lithium batteries, manganese batteries, magnesium batteries, etc.), secondary batteries (e.g., lithium ion batteries, nickel-hydrogen batteries, nickel-cadmium batteries, zinc batteries, redox flow batteries, etc.), capacitors, and fuel cells, regardless of whether the batteries are aqueous or non-aqueous.

Claims

[Claim 1] A separator for an electrochemical element, comprising a fiber structure, inorganic particles, and a binder component supporting the inorganic particles on one main surface of the fiber structure, a specific surface area of ​​the one principal surface of the fiber structure is smaller than a specific surface area of ​​the other principal surface of the fiber structure; The binder component contains a polyvinylidene fluoride resin, the amount of the resin present on the one main surface side is greater than the amount of the resin present on the other main surface side; Separator for electrochemical elements.

Citation Information

Patent Citations

  • Lithium secondary battery and manufacture of its positive electrode

    JP2000311684A

  • Carrier device of electrode material, manufacturing device of secondary battery, and manufacture of secondary battery

    JP2000340217A

  • Lithium ion secondary battery and separator thereof

    JP2004253380A

  • Separator, and nonaqueous electrolyte battery

    JP2011165660A

  • Separator for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery

    JP2016111001A